Specific immune response to mRNA vaccines against COVID-19 in patients receiving allogeneic stem cell transplantation for myeloid malignancy was altered by immunosuppressive therapy - Macková, Jana; Hainz, Petr; Kryštofová, Jitka; Roubalová, Kateřina; Šťastná-Marková, Markéta; Vaníková, Šárka; Musil, Jan; Vydra, Jan; Němečková, Šárka (Leukemia research, 2023)
BACKGROUND: Allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients are at high risk of complications associated with COVID-19 infection due to dysfunction of their immune system. Vaccination can protect from the adverse consequences of COVID-19. However, studies on the efficacy of COVID-19 vaccines in HSCT recipients with insufficient post-HSCT immune reconstitution are still scarce. In our study, we determined how immunosuppressive medication and the reconstitution of the cellular immune system influenced T cell responses specific for the surface glycoprotein of SARS-CoV-2 virus (S antigen) after two doses of mRNA vaccine against COVID-19 in patients with myeloid malignancies treated with HSCT. METHODS: Vaccination outcomes were followed in 18 (allo-HSCT) recipients and 8 healthy volunteers. The IgG antibodies against SARS-CoV-2 spike (S) and nucleocapsid (NCP) protein were determined in ELISA and S-specific T cells were detected using a sensitive ELISPOT-IFNγ based on in vitro expansion and restimulation of T cells in pre- and post-vaccination blood samples. Multiparametric flow cytometry analysis of peripheral blood leukocyte differentiation markers was employed for determination of reconstitution of the main subpopulations of T cells and NK cells at month 6 after HSCT. RESULTS: S- specific IgG antibody response detected in 72% of the patients was lower than in healthy vaccinees (100%). Vaccine-induced T-cell responses to S1 or S2 antigen were significantly reduced in HSCT recipients, which were treated with corticosteroids in dose 5 mg of prednisone- equivalents or higher during the vaccination period or in preceeding 100 days in comparison with recipients un-affected with corticosteroids. A significant positive correlation was found between the level of anti-SARS-Cov-2 spike protein IgG antibodies and the number of functional S antigen-specific T cells. Further analysis also showed that the specific response to vaccination was significantly influenced by the interval between administration of vaccine and transplantation. Vaccination outcomes were not related to age, sex, type of mRNA vaccine used, basic diagnosis, HLA match between HSC donor and recipient, and blood counts of lymphocytes, neutrophils, and monocytes at the time of vaccination. Multiparametric flow cytometry analysis of peripheral blood leukocyte differentiation markers showed that good humoral and cellular S-specific immune responses induced by vaccination were associated with well-reconstituted CD4+ T cells, mainly CD4+ effector memory subpopulation at six months after HSCT. CONCLUSIONS: The results showed that both humoral and cellular adaptive immune responses of HSCT recipients to the SARS-CoV-2 vaccine were significantly suppressed by corticosteroid therapy. Specific response to the vaccine was significantly affected by the length of the interval between HSCT and vaccination. Vaccination as early as 5 months after HSCT can lead to a good response. Immune response to the vaccine is not related to age, gender, HLA match between HSC donor and recipient, or type of myeloid malignancy. Vaccine efficacy was dependent on well-reconstituted CD4+ T cells, at six months after HSCT.
Keywords: mRNA vakcíny; COVID-19 Vaccines; Antibodies; Allogeneic hematopoietic stem cell transplantation; imunita; imunoglobulin G; Neoplasms; imunosupresivní léčba; Vaccination; transplantace hematopoetických kmenových buněk; Immunoglobulin G; SARS-Cov-2; Immunity; SARS-CoV-2; Hematopoietic Stem Cell Transplantation; T cells; COVID-19; mRNA Vaccines; Immune reconstitution; vakcíny proti COVID-19; lidé; nádory; Humans; Immunosuppression Therapy